SAP UI Frameworks for Enterprise Developers A Practical Guide - Obert, Marius; Buzek, Volker (Berkeley, CA : Apress : Imprint: Apress, 2023)
Dive into the world of SAP UIs and begin your journey to becoming a development expert. In this book, you will learn the latest cutting-edge web technologies and gain a comprehensive understanding of the user experience concept that undergirds the SAP Fiori design system. SAP UI Frameworks for Enterprise Developers is filled with hands-on tutorials that will guide you through every step of the development journey, from setting up your coding editor to building your first application using UI5, SAP Fiori Elements, UI5 Web Components, or Fundamental Library Styles. Authors Marius Obert and Volker Buzek understand that staying ahead in the rapidly evolving UI technology landscape can be challenging, so they've included insights into upcoming industry-wide trends and future innovations. This book will provide you with the knowledge and skills needed to build intuitive applications with an eye-catching, SAP Fiori-conforming user interface. Don't miss this opportunity to take your UI development skills to the next level! You will: Gain an overview of the technologies that can be used to implement enterprise-ready UIs that can be deployed in the cloud as well as on-premises Discover resources for connecting with domain experts to stay on top your game and learn about innovations in the SAP ecosystem Survey industry-wide technologies trends, like micro frontends and SSR, and relate these trends to both enterprise software and new projects led by SAP.
Chapter 1: Introduction to Enterprise User Interfaces -- Chapter 2:The Siblings: OpenUI5 and SAPUI5 -- Chapter 3:The Big One: SAP Fiori Elements -- Chapter 4:The Standardized One: UI5 Web Components -- Chapter 5:The Basic One: Fundamentals Library -- Chapter 6: Industry Trends and Their Impact on the SAP Universe -- Chapter 7: Staying on Top of the Ball.
Keywords: Business information services; Internet programming; Cloud Computing; Enterprise Architecture; Web Development; Cloud Computing